HARMONIZING RELIGIOUS COEXISTENCE THROUGH EDUCATION AND POLITICAL ECONOMY: A CASE STUDY OF PANDOWOHARJO VILLAGE - Mukotip, Mukotip; Muslim, Azis; Jamil, Muhammad Abdun; Kusuma, Danar; Azka, Ibnu (Al-Qalam, 2024)
The life of the Pandowoharjo people in the framework of harmony has been going on for a long time. Pandowoharjo Village is 1 of 75 villages in Bantul district, which administratively consists of 16 hamlets and 94 RTs, with a population in 2023 of 22,818 people. In this village, the majority of people are Muslim, reaching 93%, Catholics 3%, Christians 1% and Hindu-Buddhists below 1%. However, people can live side by side without conflict and are able to construct religious coexistence in daily life. The aim of this research is to find out how education and political economy can build coexistence in society. The research method used is a qualitative method. The research results show that; 1) Education has an important role in building coexistence, this is to provide understanding and a basic foundation for society. So far, there are various religious organizations that are active in community religious activities, and there are also religious leaders who call for the importance of maintaining religious coexistence. 2) Political economy is an important sector in efforts to maintain a harmonious life. In Pendoharjo Village, the entire community can access various sectors, including economic, political and educational, regardless of religious background. This is proof that Pandowoharjo Village has been able to construct coexistence in all aspects of life.